Explainable machine learning and deep learning - Liao, Zhongtian (Nanyang Technological University, 2023)
The ability of machine learning to improve research, processes and products is significant. Nonetheless, one major challenge hindering its adoption is that computers do not provide explanations for the predictions made in general. This project aims to solve this problem by focusing on methods for making machine learning models and decisions made interpretable to humans.